EFECTO DEL PLOMO EN EL CRECIMIENTO DE PLÁNTULAS DE Acacia macracantha Humb. & Bonpl. ex Willd. “espino” EN CONDICIONES DE LABORATORIO (Sagasteguiana, 2017)
El Perú posee una gran variedad de especies vegetales adaptadas para vivir en suelos contaminados con altas concentraciones de metales pesados sin alterar su fisiología y crecimiento. Por ello el objetivo del presente trabajo fue determinar el efecto del plomo en el crecimiento de plántulas de Acacia macracantha Humb. & Bonpl. ex Willd. “espino” en condiciones de laboratorio. Se utilizó un diseño experimental de estímulo creciente con cinco tratamientos y tres repeticiones, utilizando 30 plántulas para cada tratamiento (0, 50, 100, 200 y 400 mg Pb/L), en un sistema hidropónico. Los resultados, a los 45 días, indican que el plomo causó efecto en 400 mgPb/L, así mismo se observó una serie de alteraciones morfológicas (clorosis, necrosis) y mayor cantidad de bioacumulaciòn de plomo se encontró en parte aérea (3.904 mgPb/g.).Palabras claves: Acacia macracantha; plántulas; plomo; crecimiento.ABSTRACTPeru has a wide variety of plant species adapted to live in contaminated with high concentrations of heavy metals without altering their physiology and growth soils. The aim of this study was to determine the effect of lead on the growth of seedlings of Acacia macracantha Humb. & Bonpl. ex Willd. "hawthorn" in laboratory conditions. Increasing stimulus experimental design was used with 5 treatments and three replications, 30 seedlings placed in each container, at concentrations of 0, 50, 100, 200 and 400 mgPb / L in a hydroponic system. The results were taken at 45 days, the results indicate that lead caused impact on the T5, in root length 9.06 cm, stem length 9.55 cm, number of secondary roots 10,  sheets 11, fresh weight (0.06 g) and dry (0.04 g) of root fresh weight (1.19 g) and dry (0.21g) of aerial part (leaves and stems), protein content: Following 3,025 mg/g, leaves 3,269 mg/g stalk 5,092 mg/g, chlorophyll a 2.33 mg/ml and carotenes 0.36 ug/ml, also present a series of morphological changes (chlorosis, necrosis). Most bioaccumulation of lead was found in aerial parts of T5, the value of 3,904 mgPb / g.Keywords: Acacia  macracantha; seedlings; lead; growth.